The role of anti-phenolic glycolipid-1 serological test in leprosy - Ni Luh Putu Ratih Vibriyanti Karna; Anak Agung Indah Jayanthi; Desak Nyoman Trisepti Utami (Explorer Front, 2022)
The number of new leprosy cases in the world is surprisingly high, Indonesia is still at the third rank in the term of new leprosy cases over the world. Leprosy control strategies can be successful if early diagnosis and appropriate therapy are carried out. Currently, several serological tests have been developed which can help detecting subclinical leprosy, making the diagnosis,and monitoring therapy. One such serological tests is the anti-Phenolic Glycolipid-1 (PGL-1) serological test. The antibody response to PGl-1 is mainly IgM, the amount of this antibody is correlated to the number of bacteria; so, the titer is higher in lepromatous type compared with tuberculoid type, this causes serological tests still have limitation in diagnosing leprosy, especially in paucibacillary type leprosy.